Diabetic retinopathy and other retinal vascular measures with the risk of cardiovascular events: a cohort study of type 2 diabetes in Singapore - Lee, Yeu Hann (Nanyang Technological University, 2024)
Background. While cardiovascular disease risk assessment is needed to inform clinical decisions, predicting individual risk in diabetics remains challenging. The evidence base regarding the effect of diabetic retinopathy on cardiovascular disease risk in a multi-ethnic Asian diabetic population is lacking.